Analisis Persepsi Masyarakat terhadap Pemilihan Rumah KPR Bersubsidi: Perspektif Manajemen Investasi dan Properti dalam Pengembangan Perumahan Perkotaan - Ni Made Ayu Juli Andjani (Institut Teknologi Garut, 2025)
This study used a questionnaire survey of 100 respondents from five housing complexes in Palu City (Tondo, Duyu, Mamboro, Kawatuna, Pengawu) to examine people's perceptions of subsidized mortgage homes compared to rental housing. Respondents consisted of students, office workers, and entrepreneurs with different needs: students were looking for affordable housing close to campus, office workers prioritized long-term investment, and entrepreneurs needed economic assets. The majority of respondents chose subsidized mortgage houses because of affordable installments, property ownership, and long-term security, while rental housing was considered less stable. These findings emphasize the importance of fund management, risk, and building quality in property investment and construction management, and serve as the basis for developing effective and sustainable subsidized housing programs for all parties involved.